Bridging gaps in music teacher education : developing exemplary practice models using peer collaboration. - Ballantyne, Julie; Barrett, Margaret; Harrison, Scott; Temmerman, Nita (Australian Learning and Teaching Council, 2009)
This project provided a cross-institutional framework for the development of a contextualised and integrated learning resource for music teacher education. A primary achievement of the project was the Music Teachers Oz (MTO) website, developed during the course of the project. This online forum and learning tool provided pre-service teachers, teachers, academics, members of the MTO team and the general public with the opportunity to interact and discuss issues surrounding music education. [Executive summary]